The impact of financial development institutions on the financing of the agro-industrial sector in Kazakhstan - Aubakirova М.; Makysh С.; Kozak, S. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2025)
Abstract. This article examines the main areas of financing of the agro-industrial complex by the Government of the Republic of Kazakhstan, and also raises the question of the degree of influence of financial development institutions in this industry. Currently, the transience of changes in politics, economics and climate around the world is extremely leading to instability in the global agricultural and food markets. As a result, government support in the small agribusiness sector in the country is an integral and important part of economic development. The country’s food security is the development of agriculture. The purpose of this article is to analyze the current state and features of financing the agricultural sector in Kazakhstan through financial development institutions, identify the impact on the availability of financial resources, and develop recommendations for improving financing mechanisms, taking into account current economic realities and government support programs. The article provides an analysis of the activities of financial development institutions in providing support in the agro-industrial sector by financing investment projects. The development of the agricultural sector, increasing the competitiveness and sustainability of agricultural enterprises are important economic indicators in the development of this sector of the economy. The relevance of the article lies in seeing the picture of the development of the country’s agricultural sector through the prism of the activities of financial development institutions.